(untitled) (Practitioner Research, 2022)
Most English language teaching classes do not teach language listening strategies nor skills. Due to this, most students especially those in rural areas will not be able to perform well in listening activities and tasks. This research looks at the perceptions and understanding of students in a rural school on their listening strategies. Open-ended questionnaire was used along with focus group discussions and semi-structured interviews looking at their awareness and usage of listening strategies in ESL classrooms. Most of the students are indigenous, therefore, they mentioned that they hardly use any strategies and they are not aware of those strategies. Findings also indicated they find the strategies to be not useful since they do not see the reasons for using these strategies due to their background. Although they felt that they have no reasons to use or study these strategies, they do admit that it will be useful as this could help to sharpen their listening skills.